Investigating Inhibitory Effects of Punica granatum Fruit Extracts on Lipid Peroxidation in the Fenton Reagent Environment - Ozsahin, Ayse Dilek; Kirecci, Oguz Ayhan; Yilmaz, Okkes; Erden, Yavuz; Bircan, Burak; Karaboga, Zeynep (Asian Journal of Chemistry, 2012)
In this study, it is aimed to find antioxidant activity of methanolic extract of Punica granatum fruit, by determining alpha,alpha-diphenyl-beta-picrylhydrazyl (DPPH) radical scavenging property and also by determining the capacity to prevent the formation of lipid peroxidation which is found in in-vitro environment that soybean and corn oils are found. The capacity of preventing lipid peroxidation was analyzed in an in vitro environment that oil samples were existed by evaporating methanol phase of extracts. In the experiment, the groups were formed as control group e.g., Fenton reactive, Pomegranate extract + Fenton reactive. It was observed that the lipid peroxidation level formed on the oils had increased at a significant level when compared to Fenton reactive groups according to the control group. When the extract groups are compared (to each other) according to the Fenton reactive group, it was detected that lipid peroxidation level had significantly decreased (p < 0.0001). According to the scavenging activity of alpha,alpha-diphenyl-beta-picrylhydrazyl radical, it was determined that the pomegranate extracts were effective at their highest level at 250-500 mu L (p < 0.0001). It was concluded that Punica granatum effectively decreases the lipid peroxidation level, neutralizes the alpha,alpha-diphenyl-beta-picrylhydrazyl free radical and has a characteristic of conserving the fatty acid content.
Keywords: Lipid peroxidation; Punica granatum; Fatty acid; Antioxidant capacity